A porous media transport model for apple drying. (December 2018) - Kumar, Chandan; Joardder, Mohammad U.H.; Farrell, Troy W.; Millar, Graeme J.; Karim, Azharul
Abstract : A comprehensive multiphase porous media model was developed and validated for apple drying. Thermal, transport, and structural properties of apple required to develop such model were formulated and presented. The model considered the transport of liquid water by capillary diffusion and gas pressure, and the transport of vapour by binary diffusion and gas pressure. A non-equilibrium formulation was used to calculate the evaporation rate, which enabled the separate illustration of vapour and liquid water transport. The equations were solved by finite element method (FEM) using physics-based modelling and a simulation platform (COMSOL Multiphysics). The model predictions were validated using experimental data and good agreement was found. Spatial distribution of liquid water and vapour saturation curves showed that the saturation levels were lower on and near the surface compared to the centre of the food material. The convective and diffusive fluxes of liquid water and vapour were presented, and this data suggested that the fluxes were higher on and near the surface of the sample. Highlights: A non-equilibrium multiphase porous media model is developed and validated. Thermo-physical properties of apple are formulated or gathered. Evolution of vapour pressures and evaporation during drying are illustrated. Water and vapour fluxes due to different sources are presented and discussed.